Influencing perception of COVID-19 illness and vaccines using an educational intervention tool in a lower-middle-income country - Jibril, Huzefa; Zaman, Muhammad Ahmed; Saadat, Eisha; Bin Zafar Mahmood, Saad; Awan, Safia; Arshad, Ainan (Journal of the Pakistan Medical Association, 2024)
The case-control study was planned to determine if an educational intervention tool could reduce coronavirus disease-2019 vaccine hesitance and resistance in people visiting a tertiary care hospital in a developing country. Participants were randomly enrolled into intervention group A and control group B from July to December 2021. Participants in group A reviewed an educational intervention tool prior to completing a questionnaire, while participants in group B did not. Responses from 440 participants were included in the final analysis. The use of the educational intervention tool significantly lowered beliefs in conspiracy theories and the impression that coronavirus disease-2019 was a simple flu that did not lead to any serious illness. It also resulted in higher levels of confidence in the effectiveness of the coronavirus disease-2019 vaccines available in the country. Of the 440 subjects, 228(51.8%) were in group A and 212(48.2%) in group B. Before reading the educational intervention, .........Cont.